Individual Investors and Corporate Bonds Market. Evidence from Poland - Gemra, Kamil; Maruszewski, Janusz (Polscy inwestorzy indywidualni na rynku obligacji korporacyjnych, 2024)
Aim: The aim of this article was to identify the preferences of individual investors in the context of investing in corporate bonds. Methodology: The study was based on two questionnaire studies with closed questions, conducted in 2018 and 2024. Findings: Firstly, the interest in investing in corporate bonds has been decreasing on the part of individual investors surveyed, while at the same time their investment portfolio has increased. Secondly, investors in both 2018 and 2024 indicated the same main factors that helped them in their investment decisions. Thirdly, the attitude towards the issuers’ industries has changed. Implications: The study has a high implicative value for corporate bond issuers, indicating areas that are important for individual investors Originality/value: The article supplements the literature with the results of a survey on the area of corporate bonds in Poland.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 2, s. 27-35
Keywords: bonds; corporate bonds; capital market; obligacje; obligacje korporacyjne; rynek kapitałowy